Development of the children's primitive reflex integration assessment scale - Wang, Meng; Yu, Jing; Li, Hongyao; Zhao, Chongran; Li, Yichao; Yang, Xinyue (Frontiers in Psychology, 2025)
ObjectiveNon-integrated primitive reflexes (PRs) in children can lead to issues in motor function and psychological wellbeing, while prior studies have shown correlations between PR integration and neurodevelopmental disorders in children. However, measurement methods for PR integration remain unestablished. Therefore, in the present study, we describe the development of a measurement scale for PR integration, a novel assessment tool to evaluate PR integration in children.MethodsCombining a literature review, practical experience, and results of specialized group discussions, a preliminary draft of the Children's Primitive Reflex Integration Measurement Scale (CPRIMS) was formulated. Employing a convenience sampling method, participants were selected from first and second-grade students in three primary schools in Liaoning province, Shenyang city, from May to July 2023. Item Discrimination Method (IDM), Critical Ratio Method (CRM), and Internal Consistency Coefficient Method (ICCM) were used for item analysis of pilot testing data. For formal testing data, Cronbach's α assessed the reliability of the scale, while fit indices such as chi-square value/degrees of freedom (χ2/df), Root Mean Square Error of Approximation (RMSEA), and Comparative Fit Index (CFI), along with tests of construct validity, evaluated the scale's validity.ResultsOverall, 555 participants were selected, 234 children with a mean age of 7.59 ± 0.71 years participated in the pilot testing, while 321 children with a mean age of 7.73 ± 0.71 years participated in the formal testing. CPRIMS comprises seven dimensions and seventeen items, including the Moro reflex (MR), Asymmetrical Tonic Neck Reflex (ATNR), Symmetrical Tonic Neck Reflex (STNR), Tonic Labyrinthine Reflex (TLR), Spinal Galant Reflex (SGR), Spinal Perez Reflex (SPR), and Landau Reflex (LR), explaining 88.2% of the total variance. Confirmatory factor analysis revealed a good model fit (χ2/df = 1.631, RMSEA = 0.044, NFI = 0.950, CFI = 0.980, IFI = 0.932, TLI = 0.972). Cronbach's α coefficients for the seven dimensions ranged from 0.730 to 0.945, demonstrating strong reliability.ConclusionCPRIMS, which includes dimensions such as MR, ATNR, STNR, TLR, SGR, SPR, and LR, demonstrates strong reliability and validity, indicating that this measure could serve as a reliable and effective tool for assessing the integration levels of PRs in children aged 6 to 9 years old.